Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1461355718763467
|View full text |Cite
|
Sign up to set email alerts
|

They can’t safeguard you when they are under stress

Abstract: The purpose of this research is to explore work-related stress in the police of Azad Jammu and Kashmir (AJ&K), Pakistan. The research aims to identify factors that contribute most towards job stress in AJ&K police and study the nature of and reasons underlying these factors. Political and media pressure has not been widely studied within the context of job stress in the police, and researchers have attempted to bridge this gap and make a theoretical contribution by highlighting the importance of politi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It has been well documented that police officers are exposed to potentially traumatic events at higher levels than the general population [19][20][21][22][23][24][25]. In a recent study, it was reported that 50.2% of RCMP and 36.7% of municipal/provincial police screened positively for one or more mental health disorders [9] (p. 509).…”
Section: Risk Factors Within Police Populationsmentioning
confidence: 99%
“…It has been well documented that police officers are exposed to potentially traumatic events at higher levels than the general population [19][20][21][22][23][24][25]. In a recent study, it was reported that 50.2% of RCMP and 36.7% of municipal/provincial police screened positively for one or more mental health disorders [9] (p. 509).…”
Section: Risk Factors Within Police Populationsmentioning
confidence: 99%
“…Some recent studies have highlighted issues and problems of Pakistan police and have called for more research in this area (Khan & Manarvi, 2011;Naz & Gavin, 2013;Nisar, Rasheed, & Qiang, 2018). We assume that occupational stress decreases career satisfaction in police, which subsequently decreases their job performance.…”
mentioning
confidence: 99%
“…For example, this is one of the pioneer studies that investigate the issues related to police personnel in AJ&K Pakistan. A research investigation on Pakistan police is also relevant as recent researchers (Khan & Manarvi, 2011;Naz & Gavin, 2013;Nisar et al, 2018) have called for more research studies in this area. Second, our research model does not only suggest a relation between occupational stress and job performance of employees in police but it also explains the underlying mechanism of career satisfaction.…”
mentioning
confidence: 99%
“…Also, many professions related jobs become much more stressful and can lead to depression situations. But identifying such situations is very difficult [11]. People used many methods to overcome their stressful situations and keep mental health positive, and they express their stressful emotions using many forms such as social media [12].…”
Section: Literature Reviewmentioning
confidence: 99%